modification of polystyrene co butadiene (Baghdad Science Journal, 2006)
During this research accomplish some chemical modifications on the Poly for new modified polymers with Kimaaaúah qualities, physical and unexpected new applications that the first of these chemical modifications that was completed is the introduction of a poly styrene butadiene swash and then this group